SISTEM PAKAR KERUSAKAN HARDWARE KOMPUTER DENGAN METODE BACKWARD CHAINING BERBASIS WEB - Yenita Wijayana (MEDIA ELEKTRIKA, 2019)
Computers are a major need to support human performance. Computers also often damage the hardware such as processor, memory, mouse, keyboard, hard disk, optical drive, monitor. Hardware damage is still rarely known by computer users. In this final project aims to build a knowledge-based system to diagnose damage to computer hardware or hardware in the form of websites using PHP using the waterfall model and the backward chaining method. Making a Computer Damage Expert System with Web-Based Backward Chaining Method is expected to be able to help computer users to solve problems on computer hardware, so users can save on technician costs and can save time.